The Duke of Caladan - Herbert, Brian; Anderson, Kevin J., 1962- (TOR, 2020)
"Leto Atreides, Duke of Caladan and father of the Muad'Dib. While all know of his fall and the rise of his son, little is known about the quiet ruler of Caladan and his partner Jessica. Or how a Duke of an inconsequential planet earned an emperor's favor, the ire of House Harkonnen, and set himself on a collision course with his own death. This is the story."--Provided by publisher.